ANALISIS PELARASAN PELAGUAN AZAN MAGRIB JOGJA TV MUADZIN RANU DIANTO - MUHAMMAD RIO EFENDI (CENDEKIA: Jurnal Ilmu Pengetahuan, 2022)
This study aims to analyze the chanting of the call to prayer naturally through empirical experience. Various environmental factors underlie Ranu's call to prayer which is categorized as a call to prayer with a Javanese tone. This research arises because of a musical phenomenon related to the acculturation of Islamic and Javanese elements. The call to prayer itself is rooted in Islam and Ranu's call to prayer comes from the Javanese culture of Yogyakarta. Ranu's call to prayer was motivated by his activities in sound art from childhood to adulthood as a courtier of the Yogyakarta Palace. The phenomenon of the song caused various controversies from various circles, but not a few also responded positively. Musical communication is one of the impacts, including Jogja TV's interest in broadcasting the call to prayer, as well as being discussed by various elements in the surrounding community and at large. The support from the Yogyakarta Palace became real because of the positive response that was framed from the concept of musical communication. This study uses an ethnomusicological approach by using the concept of tuning in the form of measuring the frequency of the tone, sorting the notes and their range, and identifying the family of tuning. This study was conducted through qualitative research using ethnographic methods and using observation data collection techniques, literature studies, and interviews. The results of the analysis found that there was a musical tuning system of Ranu Dianto's call to prayer. The tuning system is included in the slendro barrel area, although some of them have a difference between the pitch range and the gembyang range. This is because the appropriateness of the human voice, especially Ranu Dianto, is different from the gender instrument barung laras slendro gamelan Harjanegara Yogyakarta Palace. ABSTRAKPenitian ini bertujuan untuk menganalisis pelaguan azan secara alami melalui pengalaman empiris. Berbagai faktor lingkungan mendasari adanya pelaguan azan Ranu yang dikategorikan azan dengan rasa nada Jawa. Penilitian ini muncul karena adanya sebuah fenomena musikal yang berhubungan dengan akulturasi unsur Islam dan Jawa. Azan itu sendiri berakar dari Islam dan pelaguan azan Ranu bersumber dari budaya Jawa Yogyakarta. Pelaguan azan Ranu dilatarbelakangi oleh kegiatannya olah seni suara mulai sejak kecil hingga dewasa menjadi abdi dalem Keraton Yogyakarta. Fenomena pelaguannya menimbulkan berbagai kontroversi dari berbagai kalangan, namun tidak sedikit pula yang merespon positif. Komunikasi musikal merupakan salah satu dampaknya, diantaranya ketertarikan Jogja TV menayangkan azan tersebut, serta menjadi pembahasan dari berbagai elemen di masyarakat sekitar maupun secara luas. Dukungan dari pihak Keraton Yogyakarta menjadi riil adanya respon positif yang terbingkai dari konsep komunikasi secara musikal. Penelitian ini menggunakan pendekatan etnomusikologi dengan menggunakan konsep pelarasan berupa pengukuran frekuensi nada, mengurutkan nada beserta jangkahnya, dan mengidentifikasi keluarga pelarasan. Kajian ini dilakukan melalui penelitian kualitatif dengan metode etnografi dan menggunakan teknik pengumpulan data observasi, studi pustaka, dan wawancara. Hasil analisis menemukan adanya sistem pelarasan secara musikal dari pelaguan azan Ranu Dianto. Sistem pelarasan tersebut masuk dalam wilayah laras slendro, meskipun beberapa di antaranya memiliki selisih antara jangkah nada dan jangkah gembyang. Hal ini disebabkan kepantasan rasa suara manusia khususnya Ranu Dianto berbeda dengan instrumen gender barung laras slendro gamelan Harjanegara Keraton Yogyakarta.